Jalan Ideologi Dalam Negara Demokrasi - Rocky Gerung (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2015)
This study is about the path of ideology in a democratic country. Ideology is a psychic tool. It is used to link the historical conditions of a period to their future origins. A kind of "back to the future" motion. In that mechanism it becomes absolute. Because, to "own" the future, he must glorify the past, as an excuse to "return to the future". Ideology is obsessive fantasy, which is "prayer" that guarantees the past ... in the future. In fact, ideology seeks its future into the past.